2009
DOI: 10.1016/j.trstmh.2008.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Drug resistance profile of Mycobacterium tuberculosis isolates from pulmonary tuberculosis patients in Jos, Nigeria

Abstract: The drug resistance profile of 100 Mycobacterium tuberculosis isolates from pulmonary tuberculosis (PTB) cases in Jos, Nigeria, was investigated between August 2006 and September 2007. Drug susceptibility testing for 50 new, 11 follow-up and 39 unclassified cases of PTB was performed on Löwenstein-Jensen medium by the proportion method, using isoniazid (0.2 microg/ml), rifampicin (40 microg/ml), ethambutol (2 microg/ml) and streptomycin (4 microg/ml). Susceptibility to all four drugs was found in 76, 62 and 55… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 6 publications
4
20
0
Order By: Relevance
“…Other publications report on a streptomycin resistance rate of 11% but did not fi nd INH mono-resistant strains [2]. The low number of isolates ranging from 32 (this study) to 50 [1,2] might account for that effect. However, we identifi ed 16% of the isolates as MDR TB stains; these strains were at least resistant to INH, RMP, STR, and EMB, and one was additionally resistant to PZA.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…Other publications report on a streptomycin resistance rate of 11% but did not fi nd INH mono-resistant strains [2]. The low number of isolates ranging from 32 (this study) to 50 [1,2] might account for that effect. However, we identifi ed 16% of the isolates as MDR TB stains; these strains were at least resistant to INH, RMP, STR, and EMB, and one was additionally resistant to PZA.…”
Section: Discussionmentioning
confidence: 56%
“…Only few publications that deal with the susceptibility pattern of bacteria [1,13]. However, data collected in a tertiary hospital in Nigeria report on pan-susceptibility in only 46% of the isolated TB strains [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings from a previous study in Jos, (North Central Region) had indicated that there is a need to review the procedures for TB diagnosis and treatment in Nigeria [11].…”
Section: Introductionmentioning
confidence: 99%